RECENT EVIDENCE OF PHYSICAL ABNORMALITY IN CHILDREN WITH LEARNING DISABILITIES - Pihl, Robert O. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1979)
The idea that the difficulties of "learning-disabled" children have a physical explanation rather than a purely psychological one has been in prolonged abeyance. but has recently experienced a powerful resurgence. Pihl reviews recent findings from a number of fields in physiology, and adds to them an account of his own discovery that these disabilities appear to be strongly related to the presence in the body of above-normal levels of certain elements - not only lead, but also lithium and others. These developments point to the clear prospect of our developing forms of intervention by nutrition and other physical means that may bring success where purely educational interventions have faced apparently intractable problems.